Aspectos do manejo integrado da mosca minadora e conservação de polinizadores em meloeiro - Costa, Ewerton Marinho da (Universidade Federal Rural do Semi-Árido, 2016)
The aims of this study were to measure the damaged leaf area and evaluate the physiological responses of plants of melon (Cucumis melo L.) submitted to different levels of infestation per larvae of Liriomyza sativae Blanchard, evaluate the natural parasitism of larvae of said pest and check the toxicity of insecticides used in the management of insect pests of culture on A. mellifera. Each objective corresponds to a chapter of the work. Damaged leaf area and physiological responses of the melon plants submitted the different levels of infestation of leafminer: The study was conducted in a greenhouse and the infestation levels were: 0 (no infestation leaves), 1; 10 ± 0.4; 20 ± 0, 9 and 30 ± 1.3 larvae per leaf. We observed averages the damaged leaf area of 1.2 cm2, 6.3 cm2, 19.6 cm2 and 40.8 cm2 for infestations of 1; 10 ± 0.4; 20 ± 0.9 and 30 ± 1.3 larvae/leaf, respectively. With respect to the physiological aspects, the rate of photosynthesis, stomatal conductance and transpiration significantly decreased with the increase of leafminer larvae per leaf. On the other hand, the internal CO2 concentration increased with the increase in the number of larvae per leaf. Natural parasitism of larvae the leafminer in the melon crop in semiarid of Rio Grande do Norte state, Brazil: The study was conducted in areas of commercial production of melon, located in the rural zone municipality of Mossoró-RN, during of period growing season of two agricultural years, 2012-2013 and 2013-2014. We identified the parasitoids Opius scabriventris Nixon and Neochrysocharis sp. parasitizing larvae of the leafminer during of the two agricultural years. It was found that Neochrysocharis sp. presented higher means of parasitism than O. scabriventris throughout the evaluation period of the first year and in the second year O. scabriventris excelled relative to Neochrysocharis sp. in the beginning and mid growing season. During the crop cycle, regardless of the period of each growing season, of two years of evaluation, there was an increase in parasitism with development of melon plants, and parasitism peaks in the moment of fruits harvest. Toxicity of insecticides used in the Brazilian melon crop to the honey bee Apis mellifera under laboratory conditions: The bees were exposed to insecticides abamectin, acetamiprid, cartap chloride, chlorfenapyr, cyromazin, deltamethrin, thiamethoxam, flufenoxuron and pyriproxyfen at the highest dosages recommended by the manufacturers for pest control in melon crop. Exposure to the insecticides was performed via direct spray, feeding the bees with diet contaminated with insecticide and through contact with sprayed leaves. Results indicated that, regardless of how the bees were exposed to insecticides, thiamethoxam, abamectin, and chlorfenapyr were extremely toxic to adults of A. mellifera. Acetamiprid, deltamethrin and cartap chloride were most toxic when directly sprayed on the bees. Cyromazin and pyriproxyfen caused low mortality rates to A. mellifera, whereas flufenoxuron caused moderate mortality when fed to adult bees
Aspects of integrated management of leafminer and conservation Pollinators in the melon
Keywords: Melon; Pollinators; Leafminer; Pests - management integrated; Melão; Polinizadores; Mosca minadora; Pragas - manejo integrado; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA